2022
DOI: 10.3389/fimmu.2022.861459
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated of ANXA3, SORL1, and Neutrophils May Be Key Factors in the Progressionof Ankylosing Spondylitis

Abstract: IntroductionThe specific pathogenesis of ankylosing spondylitis (AS) remains unclear, and our study aimed to investigate the possible pathogenesis of AS.Materials and MethodsTwo datasets were downloaded from the GEO database to perform differentially expressed gene analysis, GO enrichment analysis, KEGG pathway analysis, DO enrichment analysis, GSEA analysis of differentially expressed genes, and construction of diagnostic genes using SVM and WGCNA along with Hypoxia-related genes. Also, drug sensitivity analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 44 publications
(37 reference statements)
1
24
0
Order By: Relevance
“…Single-cell RNA sequencing revealed altered NK cells subsets in peripheral circulation of AS patients (34). Increased of neutrophils may be a primary factor in the AS progression (35). These studies revealed that signi cance of immune cell in ltration in the etiopathogenesis of AS.…”
Section: Discussionmentioning
confidence: 81%
“…Single-cell RNA sequencing revealed altered NK cells subsets in peripheral circulation of AS patients (34). Increased of neutrophils may be a primary factor in the AS progression (35). These studies revealed that signi cance of immune cell in ltration in the etiopathogenesis of AS.…”
Section: Discussionmentioning
confidence: 81%
“…NETs are the first immune cells to infiltrate the intestinal barrier, and extensive infiltration of NETs is positively correlated with active UC (41). Jiang et al reported that the upregulation of neutrophils may be a key factor in the progression of AS (42). Interestingly, most of the evidence accumulated thus far points to adaptive immunity being related to AS pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al. reported that the upregulation of neutrophils may be a key factor in the progression of AS ( 42 ). Interestingly, most of the evidence accumulated thus far points to adaptive immunity being related to AS pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that there are fewer working neutrophils in the tissues could explain Computational and Mathematical Methods in Medicine why fungi are harder to stop, and the risk of intestinal inflammation is higher [40]. There were also reports that the severity of AS was strongly connected to neutrophils [41,42]. Recently, Zhou et al found that in addition to neutrophils, monocytes were also associated with AS infiltration and identified LYN as a hub gene [43].…”
Section: Discussionmentioning
confidence: 99%